Conducting Virtual, Synchronous Focus Groups Among Black Sexual Minority Men: Qualitative Study - Dangerfield II, Derek T; Wylie, Charleen; Anderson, Janeane N (JMIR Publications, 2021)
BackgroundFocus groups are useful to support HIV prevention research among US subpopulations, such as Black gay, Black bisexual, and other Black sexual minority men (BSMM). Virtual synchronous focus groups provide an electronic means to obtain qualitative data and are convenient to implement; however, the protocols and acceptability for conducting virtual synchronous focus groups in HIV prevention research among BSMM are lacking. ObjectiveThis paper describes the protocols and acceptability of conducting virtual synchronous focus groups in HIV prevention research among BSMM MethodsData for this study came from 8 virtual synchronous focus groups examined in 2 studies of HIV-negative BSMM in US cities, stratified by age (N=39): 2 groups of BSMM ages 18-24 years, 5 groups of BSMM ages 25-34 years, and 1 group of BSMM 35 years and older. Virtual synchronous focus groups were conducted via Zoom, and participants were asked to complete an electronic satisfaction survey distributed to their email via Qualtrics. ResultsThe age of participants ranged from 18 to 44 years (mean 28.3, SD 6.0). All participants "strongly agreed" or "agreed" that they were satisfied participating in an online focus group. Only 17% (5/30) preferred providing written informed consent versus oral consent. Regarding privacy, most (30/30,100%) reported "strongly agree" or "agree" that their information was safe to share with other participants in the group. Additionally, 97% (29/30) reported being satisfied with the incentive. ConclusionsConducting virtual synchronous focus groups in HIV prevention research among BSMM is feasible. However, thorough oral informed consent with multiple opportunities for questions, culturally relevant facilitation procedures, and appropriate incentives are needed for optimal focus group participation.